Management Of Second-Degree Internal Haemorrhoid With Apamarga Pratisarneeya Teekshna Kshar- A Case Report - Patel, Shekhar; Sahu, Shraddha; Singh, Narinder; Kumar, P Hemantha (International Research Journal of Ayurveda & Yoga, 2020)
A 45-year male patient reported to Shalya Tantra OPD in National institute of Ayurveda Jaipur with complaints of something coming out from anal verge since last 2 years with occasional bleeding in the form of drops and splashes per-anum. After thorough examination the patient was tagged with the diagnosis of Arsha (Second degree internal haemorrhoid). The patient was Planned for kshara karma (Kshar Pratisaaran) on oct.10th 2018 with very encouraging outcome. Apamarga Pratisaraneeya teekshna kshara was found to be effective in the second-degree haemorrhoid mass within 21 days of application. After follow up of 6 month no recurrence of any presenting complaint was observed.